Visiones letradas sobre el español americano en la etapa de transición republicana - Prieto Rojas, Fernando (2024)
In the 19th century, the role of Spanish as an identity symbol in the new American nations was uncertain. Although it was the language inherited from a recently overthrown monarchy, its ability to unite and represent the emerging republics sparked various debates. Thinkers like Juan León Mera, Andrés Bello, Rufi no José Cuervo, and Clorinda Matto de Turner discussed the role of Spanish in the independence process. This work analyzes some perspectives on Hispanicization in America, exploring 19th-century linguistic and literary views on Castilianization and the use of Spanish within the context of the transition toward independent republics.